A comparative study of ductile-brittle transition behavior and fractography of P91 and P92 steel. (November 2017) - Saini, Nitin; Pandey, Chandan; Mahapatra, Manas Mohan; Narang, H.K.; Mulik, R.S.; Kumar, Pradeep
Abstract: The modified 9Cr-1Mo (P91) and 9Cr- 0.5Mo- 1.8W (P92) steel used in fast breeder reactor is exposed to irradiation during service which severely affects the dynamic fracture resistance by increasing the ductile to brittle transition temperature (DBTT). Thus, even at room temperature, the steel can become brittle and prone to cracking. In the present investigation, to elucidate the influence of low temperature on the DBTT, Charpy toughness test was performed on creep strength enhanced ferritic P91 and P92 steel. Lower DBTT was observed for the P92 steel as compared to P91 steel. To find the mode of fracture, the fractured Charpy toughness specimens were investigated using a field electron scanning electron microscope (FESEM). The fracture surface revealed the brittle mode of fracture at a lower temperature for both the steels while the mixed mode of fracture was noticed at room temperature and above. Highlights: To elucidate the influence of low temperature on the DBTT, Charpy toughness test was performed on P91 and P92 steel. DBTT was calculated for both P91 and P91 steel. The fractured Charpy toughness specimens were investigated using a field electron scanning electron microscope (FESEM).